Eco-innovation Mobilisation Framework For Contractors In Green Development Projects - Fisol, Aimi Shahirah (2023)
The concept of eco-innovation (EI) addresses the complex issues between the construction sector and the environment to restore the balance between both elements. The impacts of a slow rate of innovation within this sector emphasise the need for contractors to use EI measures to reduce these negative effects and create a more sustainable approach to constructing while maximising economic value. Using Resource Mobilisation Theory, this research aims to develop the contractor’s eco-innovation mobilisation framework for construction projects. It has three objectives focusing on determining the components of EI at construction projects within the contractor’s scope of work, examining the conditions that influence EI mobilisation at the project, and investigating the contractor’s strategy to mobilise EI practices at the project. Through qualitative method, interviews are conducted with 15 contractors involved in the green development projects. The study found that the EI components within the contractor’s work scope consist of product EI, process EI, and organisational EI. The conditions influencing EI mobilisation are the firm capability, project nature, and external enabler. The strategies adopted by the contractor to mobilise EI are human capitalisation, smart engagement, information dissemination, extending company policy to project implementation, strengthening documentation procedures, and technology optimisation.